Impact of risk perception on customer purchase behavior: a meta-analysis. Issue 1 (6th January 2020) - Li, Zhihong; Sha, Yongzhong; Song, Xuping; Yang, Kehu; ZHao, Kun; Jiang, Zhixin; Zhang, Qingxia
Abstract : Purpose: Risk perception is an essential factor affecting how individuals evaluate risk, make decisions and behave. The impact of risk perception on customer purchase behavior has been widely studied; however, the association has been debated. Therefore, the purpose of this paper is to examine the relationship between risk perception and customer purchase behavior and to examine factors that could moderate it. Design/methodology/approach: This study conducted a meta-analysis of this relationship and examined factors that could moderate it. Six databases were comprehensively searched. Two reviewers independently selected the studies for inclusion, extracted data and assessed quality. Pearson's r was used as the effect estimate. A total of 33 studies were included in the meta-analysis. Findings: The results revealed a negative relationship between risk perception and customer purchase behavior. The geographical region, purchase channel and country development level affected the relationship. The correlation between perceived risk and purchase behavior in European consumers was the highest, followed by the correlation in American consumers; the weakest correlation was found in Asian consumers. For consumers in developed countries, perceived risk had a stronger negative influence on customer purchase behavior than that for consumers in developing countries. The perceived risk of online purchase channels had a stronger negative impact on customer purchase behavior than that of offline purchase channels. Research limitations/implications: Risk perception is a useful context in which to explain barriers to customer purchase behavior. In addition, reducing consumers' risk perception and perfecting the market transaction process with respect to buying behavior should be further studied. Originality/value: The findings of this review indicate a direct negative relationship between risk perception and customer purchase behavior. To the best of the authors' knowledge, this review is the first to meta-analytically summarize the impact of risk perception on customer purchase behavior in social sciences research, and it also illuminates new perspectives for future studies.